Catalytic-independent neuroprotection by SIRT1 is mediated through interaction with HDAC1 - Pfister, Jason A. (PLoS One, 2019)
SIRT1, a NAD+-dependent deacetylase, protects neurons in a variety of in vitro and in vivo models of neurodegenerative disease. We have previously described a neuroprotective effect by SIRT1 independent of its catalytic activity. To confirm this conclusion we tested a panel of SIRT1 deletion mutant constructs, designated Δ1–Δ10, in cerebellar granule neurons induced to undergo apoptosis by low potassium treatment. We find that deletions of its N-terminal, those lacking portions of the catalytic domain, as well as one that lacks the ESA (Essential for SIRT1 Activity) motif, are as protective as wild-type SIRT1. In contrast, deletion of the region spanning residues 542–609, construct Δ8, substantially reduced the neuroprotective activity of SIRT1. As observed with LK-induced apoptosis, all SIRT1 constructs except Δ8 protect neurons against mutant huntingtin toxicity. Although its own catalytic activity is not required, neuroprotection by SIRT1 is abolished by inhibitors of Class I HDACs as well as by knockdown of endogenous HDAC1. We find that SIRT1 interacts with HDAC1 and this interaction is greatly increased by deleting regions of SIRT1 necessary for its catalytic activity. However, SIRT1-mediated protection is not dependent on HDAC1 deacetylase activity. Although other studies have described that catalytic activity of SIRT1 mediates is neuroprotective effect, our study suggests that in cerebellar granule neurons its deacetylase activity is not important and that HDAC1 contributes to the neuroprotective effect of SIRT1.